Foliar Application of Amino Acids and Nutrients as a Tool to Mitigate Water Stress and Stabilize Sugarcane Yield and Bioenergy Generation - Jacomassi, Lucas Moraes [UNESP]; Pacola, Marcela [UNESP]; Momesso, Letusa; Viveiros, Josiane [UNESP]; Júnior, Osvaldo Araújo [UNESP]; Siqueira, Gabriela Ferraz de [UNESP]; Campos, Murilo de [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (MDPI, 2024)
Extended periods of water stress negatively affect sugarcane crop production. The foliar application of supplements containing specific nutrients and/or organic molecules such as amino acids can improve sugarcane metabolism, stalk and sugar yields, and the quality of the extracted juice. The present study assessed the effectiveness of the foliar application of an abiotic stress protection complement (ASPC) composed of 18 amino acids and 5 macronutrients. The experiments were carried out in the field with two treatments and twelve replicates. The two treatments were no application of ASPC (control) and foliar application of ASPC. The foliar application of ASPC increased the activity of antioxidant enzymes. The Trolox-equivalent antioxidant capacity (DPPH) was higher in ASPC-treated plants than in control plants, reflecting higher antioxidant enzyme activity and lower malondialdehyde (MDA) levels. The level of H2O2 was 11.27 nM g−1 protein in plants treated with ASPC but 23.71 nM g−1 protein in control plants. Moreover, the application of ASPC increased stalk yield and sucrose accumulation, thus increasing the quality of the raw material. By positively stabilizing the cellular redox balance in sugarcane plants, ASPC application also increased energy generation. Therefore, applying ASPC is an effective strategy for relieving water stress while improving crop productivity.
Keywords: antioxidant enzymes; oxidative stress; Saccharumspp; water deficit